Chemoreduction with topotecan and vincristine: Quantifying tumor response in bilateral retinoblastoma patients. Issue 4 (28th January 2021) - King, Benjamin A.; Sahr, Natasha; Sykes, April; Wilson, Matthew W.; Brennan, Rachel C.
Abstract: Background: Evaluate the efficacy of two courses of vincristine and topotecan (VT) neoadjuvant intravenous chemotherapy in reducing retinoblastoma tumor volumes. Methods: Twenty‐seven patients with previously untreated, bilateral advanced retinoblastoma who were enrolled on a prospective treatment protocol (NCT00186888). Patients underwent high‐resolution ophthalmic imaging at diagnosis and were reimaged following treatment with two cycles of VT. Tumor height and diameter were measured before and after treatment, and tumor volumes were calculated. Statistical methods for dependent samples were used. Results: Imaging was completed for 75 tumors in 23 patients (43 eyes). After two cycles of VT, median decrease in tumor height was 47% and median decrease in tumor diameter was 22%. Median decrease in estimated tumor volume was 74%. Sixty‐one of 75 tumors demonstrated >50% reduction in tumor volume. Distance from the optic nerve (=0 vs >0), age (<4 vs >4 months), macular location (within vs outside), and time (pre‐ and posttreatment) were found significantly associated with log‐transformed tumor volume adjusting for the repeated effect of patient eye using generalized estimating equations to estimate the parameters of a generalized linear model ( P < .0001 [ β : 1.95, CI: 1.53‐2.36], P = .0031 [ β : 1.49, CI: 0.57‐2.41], P < .0001 [ β : .94, CI: 0.54‐1.35], and P < .0001 [ β : 1.43, CI: 1.15‐1.71]). Conclusion: Chemoreduction was achieved in all patients and most retinoblastoma tumors following two cycles of VT. Reduction in tumor dimensions was comparable to that reported with platinum‐based chemotherapy. Tumor location, distance from the optic nerve, and age at diagnosis were significant predictors of treatment response.